Transformasi Layanan SIM Nasional Presisi (SINAR) melalui Inovasi Aplikasi Digital Korlantas Polri di SATPAS Colombo Surabaya - Indracahyaning Mustikasari; Oktarizka Reviandani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implementation of public services in Indonesia is regulated by Law Number 25 of 2009, namely a series of activities to meet service needs in accordance with regulations for every citizen and resident. This service includes goods, services or administrative services provided by public service providers. In addition, through Presidential Instruction Number 3 of 2003 concerning national policies and strategies for developing E-government, communication and information technology is utilized in government processes to increase the efficiency and effectiveness of government administration. One form of e-government-based public service innovation introduced by the National Police Chief is the National Police Traffic Corps Digital application in the form of the SINAR Service with the aim of providing more effective and efficient public services in the driving license (SIM) renewal process which can be accessed online. The aim of this research is to describe the Digital Application Innovation of the National Police Traffic Corps in the SINAR (Precision National Driving License) Service at SATPAS Colombo Surabaya. This research uses a qualitative descriptive approach. The research results show that: 1) Relative Advantage, This innovation was accepted quickly, even though there were internal challenges related to the applicant's signals and devices. 2) Compatibility, acceptance of innovation is fast, but some people still don't know about SINAR services because socialization is not yet comprehensive. 3) Complexity, innovation is accepted quickly, but there are technical problems such as lag or bugs when uploading photos. 4) Triability, positive and rapid acceptance of the innovation due to internal testing by the development team, Satpas staff, as well as a two-week trial with SIM applicants that successfully identified and fixed problems, ensuring the application meets user needs. 5) Observability, innovation is accepted quickly in society, but there are still deficiencies in data collection on applicant queues by security officers that need to be considered.